The Absorption of Islamic Education Thought of KH. M. Hasyim Asy’ari through Teaching of Adab al-‘Alim wa al-Muta’allim among the Santri at the Pesantren Tebuireng - Muhammad Abror Rosyidin; Jasminto Jasminto; Jumari Jumari (Millah: Journal of Religious Studies, 2023)
K. H. M. Hasyim Asy’ari was founder and first chairman of Nahdhatul Ulama, one of the largest Islamic mass organization in Indonesia and the world. He was also a prominent scholar, with many of his books becoming the main references for Islamic boarding schools or pesantrens in Indonesia. The primary objective of this study is to systematically document, illustrate, and comprehend the cognitive absorption process of educational concepts in the book Adab al-’Alim wa al-Muta’allim, one of K. H. M. Hasyim Asy’ari’s masterpiece. This research examines the incorporation of Islamic educational philosophy in the book among santri, students of Islamic boarding school, of Pesantren Tebuireng Jombang, Indonesia. This study adopted a descriptive qualitative methodology including observational research techniques. The data collection processes involved the utilization of interviews, observations, and documentation, utilizing a snowball sampling technique. This study utilizes interactive analytical procedures consisting of three essential stages: data reduction, data presentation (also known as data display), and the formulation and validation of findings. The findings of the study indicate that a significant proportion of participants had a strong understanding of the content of the book and made concerted efforts to incorporate its teaching into their lives. Consensus was reached among all participants regarding the pedagogical significance of the book and its constructive impact on santri.